A neural network approach towards generalized resistive switching modelling - Carvalho, Guilherme (2022)
Funding: This research was funded by FEDER funds through the COMPETE 2020 Programme and National Funds through FCT—Portuguese Foundation for Science and Technology under project number DFA/BD/8335/2020. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.